Casos y cosas: semanario popular (Vol. 2, No. 52) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: ¡Antipatriotismo!, Monologo de un tipo, Apuntes de un tonto, Las solteras y el aeroplano, Correo franco y con.... franqueza, Las virtudes

ENGLISH: Antipatriotism!, Monologue of a guy, Notes of a fool, The bachelorettes and the airplane, frank mail and with.... frankness, The virtues
Cases and things: popular weekly (Vol. 2, No. 52)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas